Flow‐Through Microbial Capture by Antibody‐Coated Microsieves. Issue 3 (19th November 2014) - Nguyen, Ai T.; van Doorn, Ronald; Baggerman, Jacob; Paulusse, Jos M. J.; Klerks, Michel M.; Zuilhof, Han; van Rijn, Cees J. M.
<x xml:space="preserve">Abstract</x> A new flow‐through method for rapid capture and detection of microorganisms is developed using optically‐flat microengineered membranes. Selective and efficient capture of Salmonella is demonstrated with antibodies coated on membranes (microsieves) having a pore size much larger than the microorganism itself. The silicon‐nitride membranes are first photochemically coated with 1, 2‐epoxy‐9‐decene yielding stable Si–C and N–C linkages. The resultant epoxide‐terminated microsieves are subsequently biofunctionalized with anti‐Salmonella antibodies. The capture efficiency of antibody‐coated microsieves with different pore sizes (2.0–5.0 μm) is studied with Salmonella enterica enterica serotype Typhimurium suspensions (107 cfu mL–1). The antibody‐coated microsieves capture 52% (2 μm microsieves), 30% (3.5 μm microsieves), and 12% (5 μm microsieves) of Salmonella from the suspension. The influence of flow rate (0.8–16 μL min–1 mm–2) on the capture efficiency of antibody‐coated 3.5 μm microsieves is investigated. The capture efficiency increases from ≈30% to ≈70% when the flow‐rate decreases from 16 to 0.8 μL min–1 mm–2. Antibody‐coated 3.5 μm microsieves can capture Salmonella rapidly and directly from fresh milk suspension (capture 35% at concentration of 80 cfu mL–1). The use of antibody‐coated microsieves as microbial selective capture devices is thus shown to be highly promising for the direct capture of microorganisms.